Pendampingan Pembuatan Pupuk Organik Cair (POC) Dari Limbah Bonggol Pisang Kepok dengan Bioaktivator EM4 (Effectice Microorganism 4) Kepada Peserta Didik Prakerin SMKN I Kota Komba di STIPER Flores Bajawa - MOI MEO, MONIKA (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Excessive and continuous use of chemical/inorganic fertilizers can cause a decrease in soil fertility levels, disruption of biodiversity, increased pest attacks, so it is recommended that we return to using organic fertilizers whose ingredients we can get from the surrounding environment, such as banana tuber waste. The aim of this activity is to find out how to make liquid organic fertilizer by utilizing banana tuber waste/garbage which the people of Ngada Regency find useless and use as organic fertilizer to reduce the use of chemical fertilizers. The stages of making liquid organic fertilizer from banana humps are providing a presentation and discussion about liquid organic fertilizer, preparation of tools and materials and procedures for making liquid organic fertilizer (POC). The result of this activity is to provide special skills and knowledge for vocational students of SMK N I Komba City who are directly involved in making POC from banana tubers. Keywords: Organic Fertilizer, Inorganic Fertilizer, Liquid Organic Fertilizer (POC), Banana Weevil